Avaliação da citotoxicidade e atividade antiviral da própolis frente ao calicívirus felino (FCV), adenovírus canino 2 (CAV-2) e vírus da diarréia viral bovina (BVDV) - Cueto, Ana Paula Stricker (2010)
Viruses are etiologic agents of a great number of diseases of human beings and animals. However, there are only a little amount antiviral medicines available that is almost exclusively used in human health. Several studies have demonstrated that propolis has biological activities against virus, bacteria and fungi. Its chemical composition is diverse varying according to season, plants available and collection. The antiviral activity of ethanolic extracts of propolis have already been described for some human viruses. The aim of this study was to evaluate the antiviral activity of propolis ethanolic extracts against two viruses causing respiratory disease in small animals, the feline calicivirus (FCV) and canine adenovirus 2 (CAV-2), and also the bovine diarrheal disease virus (BVDV).Two samples of ethanolic extracts of propolis were used; one obtained in the lab and another obtained commercially. In order to perform the experiments the MTT test ((3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) was used to determine the 50% cytotoxic concentration (CC50), the 50% inhibitory concentration (IC50) and, the terapeuthic index (TI=IC50/CC50). The propolis extracts were added to the cell cultures in different moments of the viral infection. They were included before virus inoculation, after virus inoculation, and before and after virus inoculation. The two propolis samples showed similarities in the qualitative analysis but they had small differences in the quantitative analysis. The CC50 of the extracts varied among 251 and 343μg/ml and the commercial extract showed less toxicity. Both extracts demonstrated better antiviral activity when added before virus inoculation and the ITs varied from 6 to 13. The best results were obtained with the propolis extracted in the lab. The BVD was the virus showing the greater sensitivity to the ethanolic extracts in the conditions applied. Taken all the data together, it can be concluded that the ethanolic extract of propolis has a potential for future use as a medicine in the therapy of respiratory disease caused by CAV-2, and, also, that the action mechanisms on BVDV should be better evaluated in detail regarding the hepatitis C virus (HCV).